European Monetary Union at ten: Had the German Maastricht critics been wrong? - Renate Ohr (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2009)
Against the background of the euro-sceptic view many German economists expressed during the 1990ies and the traditional as well as modern debate on the optimum currency area the outcomes of the first ten years of the European Monetary Union are analysed. It is checked to what extent the concerns raised by Maastricht critics have been justified, or rather, to what extent the feared risks have not (or have not yet) materialised. It is shown that some of the alarming risks of the European Monetary Union that had been predicted in the 1990ies have emerged in the meantime even though they have not yet essentially affected the euro's stability. But it remains to be seen whether, or rather how, the euro within the framework of a non-optimal currency area will overcome the challenges of the global financial and economic crisis without a loss of stability.
Keywords: E5; F3; 330; Euro; European Monetary Union; Maastricht Treaty; Optimum Currency Area